PERBEDAAN TRADING SAHAM DAN BINARY TRADING BERDASARKAN HUKUM INDONESIA - Kasman Samosir; Djamanat Samosir; Christopher Panal Lumban (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Indonesia is experiencing difficulties in terms of determining whether a product issued is a legitimate investment product or not, the many problematic investment products have resulted in many people not wanting to invest or being afraid to invest. The binary option case that occurred some time ago has resulted in enormous losses. The rapid development of the internet also cannot be followed by adequate public literacy skills.Keywords: stocks, binary options, legality.